Indikator Mutu Prioritas Unit Pelayanan Pendaftaran di RSU Bethesda Serukam - Rubina, Tirzhana Jean; Kendrastuti, Nungky Nurkasih; Hosizah, Hosizah; Mieke Nurmalasari (Akademi Perekam dan Informasi Kesehatan Imelda, 2025)
Improving patient quality and safety (PMKP) is a key component in ensuring hospital service quality. One measurement tool used is the quality indicator, which includes the National Quality Indicator (INM), Priority Unit Quality Indicator (IMPU), and Hospital Priority Quality Indicator (IMPRS). The Registration Unit at the Medical Records Installation of Bethesda Serukam General Hospital plays a strategic role in supporting PMKP implementation. However, the unit still requires service improvements to promote systematic quality enhancement. This study aims to design a suitable priority quality indicator for the Registration Unit. A descriptive qualitative method was used, with data collected through interviews, observation, scoring, and Focus Group Discussions (FGD). The study was conducted from November to December 2024 at Bethesda Serukam General Hospital, located at Jalan Raya Singkawang–Bengkayang KM.49, Pasti Jaya Samalantan, Desa Suka Maju, Kecamatan Sungai Betung, Kabupaten Bengkayang, Kalimantan Barat. The results identified the completeness of patient identity data in the Electronic Medical Record (EMR) as the priority quality indicator. This was selected because it met the most criteria, although the current completeness rate is still low (50%). Establishing this indicator is expected to improve service quality, patient safety, and foster a culture of quality at Bethesda Serukam General Hospital.